Free access to information of public importance in theory and practice in the Republic of Serbia - Lazić, Radojica S; Dragić, Jelena (Sociološki pregled, 2022)
The right of access to information of public importance is undoubtedly one of the key principles on which democratic societies are founded, but the fact that this right has only recently been recognized as a universal human right speaks about the reluctance of countries and governments to accept the right of access to information. The right of access to information of public importance contributes to consistent respect of human rights and freedoms, decreases the risk from corruption and unethical behaviour and has a direct impact on transparency and responsibility in work, but this right must not be a right without limitations, i.e. it must not become unlimited, regardless of how much it proclaims democratic values. Freedom of public information is a derived human right, and includes the right to true, timely and objective information, as well as the right to publicly criticize and ask for an explanation of public activities and acts of authorities and other public actors. This paper, based on valid legal regulations, discusses functioning of the right of free access to information of public importance, with a special overview of security services as the most secret part of the state apparatus of authority.